Bringing Behaviour Back In “Why a behavioural perspective is needed to provide theories of action with a theory of agency” - Campbell, Colin (Advances in Social Sciences Research Journal, 2014)
It is noted that sociology is commonly described as a discipline that studies `action’ as opposed to `behaviour’. However it is argued that this position is untenable given that `action’ is itself a form of behaviour, and hence that a `behavioural’ perspective needs to be incorporated into an action or intepretivist paradigm. Two common objections to such a proposal are then considered: first that `behaviour’ is too insignificant a portion of human conduct to be of concern to sociologists, and second that behavioural and action theory perspectives are incommensurate. The latter claim embracing the related assumptions that a behavioural analysis of human conduct `from the outside’ is incompatible with an `intepretivist’ analysis `from the inside’, and that an understanding of conduct in terms of stimulus-response is incompatible with one that presumes actors to be free agents. It is then demonstrated that neither claim is tenable given that actors are also self-observers while voluntarism does not preclude action being understood as a response to a stimulus. The paper ends with a plea for sociologists to recognise that a behavioural perspective supplies just that theory of agency that is missing from most theories of action and that in restoring it they would be implementing Weber’s recipe for a discipline that seeks to gain an “interpretive understanding of social action in order thereby to arrive at a causal explanation of its course and effects”.